AN APPLICATION OF PROBIT ANALYSIS TO FACTORS AFFECTING SMALL HOLDER FARMER’S DECISIONS TO USE FERTILIZER IN OHAJI/EGBEMA AREA OF IMO STATE, NIGERIA - F.C, Anaeto; D.O, Ohajianya; E.C, Mathews-Njoku; A.O, Ani; O.C, Korie; C.O, Osuagwu; U.C, Ozor; Nnebene E, Adolph- (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
This study analyzed factors affecting smallholder farmers’ decisions to use fertilizer in Ohaji/Egbema area of Imo State, Nigeria. Primary data were obtained between April and June 2015 with structured questionnaire from 202 randomly selected smallholder farmers. Data obtained were analyzed using descriptive statistics and probit model. Factors affecting smallholder farmers’ decisions to use fertilizers were farm size, education level, extension contact, net farm income, farming experience, cost of fertilizer, and perceived soil fertility status. Mc-Fadden’s Pseudo-R2 value of 0.6879 indicates that the independent variables included in the probit model explain 69% significant proportion of the variations in smallholder farmers’ decisions to use fertilizer. The pobit model predicted 82% of the factors affecting fertilizer use by smallholder farmers. The role of extension service in improved technology use cannot be over emphasized. The distribution of fertilizers to farmers through the GSM services should be restored since it proved an effective mechanism to reach smallholder farmers in input supply and distribution